The oncogenic role of protein kinase D3 in cancer - Liu, Yan (J Cancer, 2021)
Protein kinase D3 (PRKD3), a serine/threonine kinase, belongs to protein kinase D family, which contains three members: PRKD1, PRKD2, and PRKD3. PRKD3 is activated by many stimuli including phorbol esters, and G-protein-coupled receptor agonists. PRKD3 promotes cancer cell proliferation, growth, migration, and invasion in various tumor types including colorectal, gastric, hepatic, prostate, and breast cancer. Accumulating data supports that PRKD3 is a promising therapeutic target for treatment of cancer. This review discusses the functions and mechanisms of PRKD3 in promoting tumorigenesis and tumor progression of various tumor types as well as the latest developments of small-molecule inhibitors selection for PRKD/PRKD3.